1983
DOI: 10.1002/j.1552-4604.1983.tb02706.x
|View full text |Cite
|
Sign up to set email alerts
|

Dextroamphetamine with Morphine: Respiratory Effects

Abstract: The combination of dextroamphetamine and morphine has been shown to be synergistic for analgesia and antagonistic for most other effects. However, the claim that dextroamphetamine antagonizes the respiratory depression caused by morphine has not been well substantiated. In this double-blind study, we investigated respiratory effects, including resting respiration, isohypercapnic ventilation, CO2 response, dose response, and duration of these effects with dextroamphetamine alone and in combination with morphine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Even under well-controlled preclinical laboratory, and clinical laboratory settings (Foltin and Fischman, 1992, substantial 'individual differences' emerge and this is observed in clinical settings. Some data emerge from pain treatment where the opioid and stimulant combination is used effectively (Forrest et al, 1977;Bourke et al, 1983;McManus and Panzarella, 1986;Payne, 1997 personal communication). Still, in a human laboratory study with concurrent IM morphine and d-amphetamine administration to nondependent individuals, Jasinski and Preston (1986) observed greater euphoria and mutual antagonism of side effects.…”
Section: Abuse Of and Treatment With The Opioid-stimulant Agonist-likmentioning
confidence: 99%
“…Even under well-controlled preclinical laboratory, and clinical laboratory settings (Foltin and Fischman, 1992, substantial 'individual differences' emerge and this is observed in clinical settings. Some data emerge from pain treatment where the opioid and stimulant combination is used effectively (Forrest et al, 1977;Bourke et al, 1983;McManus and Panzarella, 1986;Payne, 1997 personal communication). Still, in a human laboratory study with concurrent IM morphine and d-amphetamine administration to nondependent individuals, Jasinski and Preston (1986) observed greater euphoria and mutual antagonism of side effects.…”
Section: Abuse Of and Treatment With The Opioid-stimulant Agonist-likmentioning
confidence: 99%
“…The different patterns and time-effect functions of stimulant drugs on ventilation in the present study (monophasic increases for dmethamphetamine under the normal air conditions) and a previous study (bi-phasic changes for (±)methamphetamine and d-amphetamine under hypercapnic conditions; Elder et al, 2023) might be related to the use of different CO 2 levels in the two studies (normal air in the current study and hypercapnic in the previous study); however, d-amphetamine (0.046-0.215 mg/kg, i.v.) produced only monophasic increases in V E relative to placebo in humans even under hypercapnic conditions (3%-7% CO 2 ; Bourke et al, 1983). Another difference between the current study using rats and the previous study using mice, is that the experiments were conducted in the light cycle in the current study and in the dark cycle in the previous study (Elder et al, 2023).…”
Section: Discussionmentioning
confidence: 73%
“…d-Amphetamine also increases V E in humans under hypercapnic conditions (3-7% CO 2 ) that increase ventilation (Bourke et al, 1983). Clinical studies have shown that d-amphetamine can attenuate the ventilatory depressant effect of morphine under both normal air and hypercapnic conditions (Bourke et al, 1983;Jasinski and Preston, 1986). In rats breathing normal air, d-amphetamine attenuates fentanyl-induced changes in ex vivo respiratory parameters (i.e., increase in partial pressure CO2 and decrease in percent oxygen saturation; Moody et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A double-blind study of 7 volunteers examined the respiratory effects of combined dexamphetamine (0.215 mg/kg) and morphine (0.15 mg/kg) alone and in combination (Bourke et al 1983). Dexamphetamine, itself a respiratory stimulant, was able to sufficiently antagonise the respiratory depression caused by morphine.…”
Section: Cl'2-adrenergic Agonistsmentioning
confidence: 99%